Respuesta :

Answer:

[tex]- 5 {x}^{2} + 12x - 4[/tex]

Step-by-step explanation:

[tex]4 {x}^{2} - (3x - 2)^{2} \\ \\ = 4 {x}^{2} - [ {(3x)}^{2} - 2(3x)(2) + {(2)}^{2} ]\\ \\ = 4 {x}^{2} - [ 9 {x}^{2} - 12x + 4]\\ \\ = 4 {x}^{2} - 9 {x}^{2} + 12x - 4\\ \\ = - 5 {x}^{2} + 12x - 4[/tex]

Esther

Answer:

-5x² + 12x - 4

Step-by-step explanation:

4x² - (3x - 2)²

4x² - (3x - 2) * (3x - 2)

4x² - (9x² - 6x - 6x + 4)

4x² -1 (9x² - 6x - 6x + 4)

(4x² - 9x²) + (6x + 6x) - 4

-5x² + 12x - 4

Hope this helps!

ACCESS MORE